A cholesterol-regulated PP2A/HePTP complex with dual specificity ERK1/2 phosphatase activity - Wang, Ping-yuan (Oxford University Press, 2003)
The acute depletion of membrane cholesterol causes the concentration of pERK1/2 in caveola/raft lipid domains and the cytosol of human fibroblasts to dramatically increase. This increase could be caused by either the activation of MEK-1 or the inhibition of a pERK phosphatase. Here we describe the isolation of a high molecular weight (∼440 kDa), cholesterol-regulated pERK phosphatase that dephosphorylates both the phosphotyrosine and the phosphothreonine residues in the activation loop of the enzyme. The dual activity in the complex appears to be due to the combined activities of the serine/threonine phosphatase PP2A and the tyrosine phosphatase HePTP. Acute depletion of cholesterol causes the disassembly of the complex and a concomitant loss of the dual specificity pERK phosphatase activity. The existence of a cholesterol-regulated HePTP/PP2A activity provides a molecular explanation for why ERK activity is sensitive to membrane cholesterol levels, and raises the possibility that ERK plays a role in regulating the traffic of cholesterol to caveolae/rafts and other membranes.